Single shot adductor canal block combined with intravenous patient‐controlled analgesia can be effective as continuous adductor canal block in reducing opioid consumption and breakthrough pain after total knee arthroplasty - Sung Eun Kim; Hyuk‐Soo Han; Myung Chul Lee; Du Hyun Ro (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose The aim of this study was to compare the following three analgesic methods after Total knee arthroplasty (TKA): intravenous patient‐controlled analgesia (IV‐PCA), continuous adductor canal block (C‐ACB), and intravenous patient‐controlled analgesia combined with single shot adductor canal block (PCA + sACB). Methods Records of 482 patients undergoing primary TKA from September 2019 to September 2020 were analyzed. Patients were divided into three pain control groups: IV‐PCA (n = 180), C‐ACB (n = 173) and PCA + sACB (n = 129). Single shot adductor canal block was performed 24 h after surgery in the PCA + sACB group. Rescue opioid consumption, breakthrough pain, pain numerical rating scale (NRS), and anti‐emetics administration were measured from postoperative day (POD) 1 to POD 5. Results Rescue opioid consumption was less in C‐ACB or PCA + sACB group than in the IV‐PCA group at POD1 (p < 0.001 and p = 0.002, respectively). Patients in C‐ACB and PCA + sACB groups had less breakthrough pain (NRS > 5) than the IV‐PCA group at POD1 (p = 0.007). On POD2, C‐ACB was statistically superior to IV‐PCA (p = 0.011) in terms of breakthrough pain. Postoperative pain NRS was lower in the C‐ACB and PCA + sACB groups than in the IV‐PCA group (p = 0.025 and p = 0.019, respectively). The total number of anti‐emetics consumption was lower in C‐ACB and PCA + sACB groups than in the IV‐PCA group (p = 0.003 and p = 0.002, respectively). Conclusion PCA + sACB not only reduced patients’ need for rescue opioids, but also decreased the number of breakthrough pain and anti‐emetics compared to IV‐PCA in early postoperative days after TKA. However, C‐ACB and PCA + sACB did not differ significantly in analgesic efficacy or opioid‐related side effects. PCA + sACB can be as effective as C‐ACB for patients undergoing TKA. Level of evidence Retrospective cohort study, level III.